ANALISIS MANAJEMEN JAMINAN HALAL PERSPEKTIF MASLAHAH MURSALAH - Diah Puspita Sari; Ridwan Basalamah; Siti Aisyah (Reflektika, 2022)
The purpose of this paper is to find out the analysis of halal assurance management from the perspective of maslahah mursalah. The results of the study stated that the management of the halal assurance system involves several institutions, namely; Ministries/institutions (K/L), Halal Product Guarantee Agency (BPJPH), Halal Inspection Agency (LPH), and the Indonesian Ulema Council (MUI). Each institution has its own main duties and functions. Maslahah perspectives regarding the management of the halal assurance system include; First, each institution (BPJPH, LPH, and MUI) has its own main duties and functions so as to minimize the occurrence of throwing responsibilities at each other. Second, there are checks and balances between each institution, checks and balances are activities to control each other in order to maintain balance between institutions.